HOW DOES COVID-19 INFLUENCE CUSTOMER BEHAVIOUR IN ONLINE SHOPPING IN INDONESIA? - Hartanto, Andreas; Wella, Wella (Ultima Management : Jurnal Ilmu Manajemen, 2024)
Abstract - E-Commerce is the distribution, purchase, sale, marketing of goods and services through electronic means such as the internet or television, or other computer networks. As a digital application, a company must have its own advantages and uniqueness that can attract consumers to use its platform continuously. This study analyzes the factors of consumer behavior towards e-Commerce during COVID-19. In this study, research was carried out using a questionnaire technique that was distributed to target respondents, namely users who actively use e-Commerce. The research model used in this study adopted the model that had been done on previous study. The data analysis method used in this research is descriptive statistics and quantitative test using SPSS 25. The results of the study with the number of samples obtained in this study were 151 samples showing that the factors that influence Consumer behavior are attitudes and awareness of behavior. Keywords: Consumer Behavior; COVID-19; Digital Application; E-Commerce; Quantitative Test.